Varför förändras (inte) ordböcker? Exemplet Florinus - Larsson, Lennart (Nordiske Studier i Leksikografi, 2006)
Why do/don’t dictionaries change? The Florinus example. This article discusses changes occurring in a minor thematic dictionary, compiled by the Finnish priest Henrik Florinus and first published in 1678 in Turku under the title Nomenclatura Rerum brevissima Latino-Sveco- Finnonica. In the following hundred years, this dictionary was reissued in at least fifteen editions, the last in 1771 in Stockholm under the title Vocabularium Latino-Svecum. The article identifies and discusses the different reasons for the changes (modernisation, product development, space requirements, mistakes, supply of printing types, and modifications marking a new edition) as well as for the absence of certain changes (labour savings, the circumstance that this type of dictionary no longer was viewed as modern, and the authoritativeness of dictionaries).